AYAT RADIKAL ATAU RADIKALISME PENAFSIRAN? - Yuzaidi Yuzaidi; Winda Sari; Muhammad Akbar Rosyidi Datmi (Fakultas Ushuluddin dan Studi Islam, 2021)
AbstractRadical actions in the name of religion have been rife lately. Islam as a religion that has the most adherents in the world is inseparable from this. Even with so many radical actions taking place in the name of Islamic teachings, the consequence is the term radical Islam, fundamentalist Islam and other Islam which are eventually grouped into hardline Islam. main teachings of Islam or its interpretation. This research uses qualitative explorative research methods by exploring, understanding and interpreting related verses through the approach of the interpretation method of maudhu'i and muqarin. as well as contemporary interpretation books (bi al-ra'y) as secondary data. The results of the data analysis reveal that the verses of jihad and qital do not contain radical elements. Jihad is an effort that aims to achieve benefit. So that every Muslim is always required to always strive throughout his life. While qital (war) is a defensive effort after there is no other way except physical resistance. Even in the war there are also strict conditions. This finding is evidence that the verses of the Qur'an do not contain radical elements. Just a partial interpretation can give birth to an exclusive interpretation and potentially radicalism. Keywords: Paragraph, Interpretation, Radical